2018
DOI: 10.1038/s41586-018-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Seabirds enhance coral reef productivity and functioning in the absence of invasive rats

Abstract: Biotic connectivity between ecosystems can provide major transport of organic matter and nutrients, influencing ecosystem structure and productivity, yet the implications are poorly understood owing to human disruptions of natural flows. When abundant, seabirds feeding in the open ocean transport large quantities of nutrients onto islands, enhancing the productivity of island fauna and flora. Whether leaching of these nutrients back into the sea influences the productivity, structure and functioning of adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
311
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 254 publications
(330 citation statements)
references
References 55 publications
17
311
0
2
Order By: Relevance
“…consumption rate per individual), to provide an overall estimate of the magnitude of a function over a unit area (e.g. rates of grazing on reefs or bioerosion m −2 ) (Bellwood et al, ; Graham et al, ; Perry & Alvarez‐Filip, ). The advantage of this approach is that functional impacts can be estimated at an individual, population, species, functional group or community level and can be expressed as a rate‐based process in terms of its spatial impact (function per unit area).…”
Section: A Critical Evaluation Of Functional Traits: Implications Formentioning
confidence: 99%
“…consumption rate per individual), to provide an overall estimate of the magnitude of a function over a unit area (e.g. rates of grazing on reefs or bioerosion m −2 ) (Bellwood et al, ; Graham et al, ; Perry & Alvarez‐Filip, ). The advantage of this approach is that functional impacts can be estimated at an individual, population, species, functional group or community level and can be expressed as a rate‐based process in terms of its spatial impact (function per unit area).…”
Section: A Critical Evaluation Of Functional Traits: Implications Formentioning
confidence: 99%
“…These so‐called “internal waves” can raise nutrient concentrations in the shallows (Aston et al, ; Leichter, Stewart, & Miller, ; Wang, Dai, & Chen, ), which in turn can promote heterotrophic feeding and growth rates in corals (Fox et al, ; Leichter & Salvatore, ; Williams et al, ), and ultimately drive broad spatial transitions in benthic functional group dominance around islands (Aston et al, ). Coral reefs are also hydrodynamically connected by additional physical processes such as lagoonal outflow and surface downwelling that can move allochthonous nutrient sources between reef habitats (Williams et al, ) and, in the absence of confounding local human impacts, enhance reef productivity and function (Graham et al, ).…”
Section: Biophysical Drivers: Setting Natural Bounds On Coral Reef Ecmentioning
confidence: 99%
“…Humans are also re‐structuring coral reef microbial communities (Kelly et al, ), and promoting the abundance of disease‐causing bacteria and viruses (Dinsdale et al, ). Remarkably, human‐introduced invasive rats can lower fish growth rates and levels of herbivory on reefs by predating on seabirds that would otherwise deliver offshore nutrient subsidies to shallow waters bordering the islands (Graham et al, ).…”
Section: Socioeconomic and Cultural Drivers: A New Reality For Coralmentioning
confidence: 99%
“…Nick Graham, one of our Assistant Editors, was recently lead author for a remarkable paper in Nature (Graham et al ., ) which revealed the remarkable biotic connectivity of terrestrial and aquatic ecosystems in the northern atolls of the Chagos Archipelago, located in the central Indian Ocean. The importance of spatial subsidies of nutrients among disparate ecosystems in a recipient system was recently demonstrated in Journal of Fish Biology (Samways et al ., ), where marine‐derived nutrients were shown to enter river ecosystems through anadromous fishes.…”
Section: The Goodmentioning
confidence: 99%
“…However, Graham et al . () linked three ecosystems: rats, birds and fish. In short, his international group of researchers showed that coral islands that are rat‐free have a >750‐times greater seabird density and a 250‐times greater nitrogen deposition rate than rat‐infested islands.…”
Section: The Goodmentioning
confidence: 99%